ERRORS MADE BY THE THIRD SEMESTER STUDENTS IN USING PUNCTUATION MARKS - Wati, Meta Kartika (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
This study aims to he students? errors in using punctuation marks in writing essay. This study conducted in the third semester students at IAIN Tulungagung academic year 2013/2014. The researcher analyzed the students errors in using punctuation marks which influences to the grammatical and semantic function. The research problems in this study are what are the errors made by the third semester students at IAIN Tulungagung in using punctuation marks in writing essay and what are the dominant errors made by the third semester students at IAIN Tulungagung in using punctuation marks in writing essay. The researcher used descriptive quantitative method in this study, and found seven kinds of punctuation marks that occurred as the errors. They are comma, period, colon, semicolon, exclamation marks, question marks, and apostrophe. Those errors were classified based on Dulay?s surface strategy taxonomy (omission, addition, misformation, and misordering).